Compliance with venous thromboembolism guideline after delivery at Maternity Teaching Hospital, Erbil city, Iraq - Nawkhas, Parween M; Alalaf, Shahla K (Zanco Journal of Medical Sciences (ZJMS), 2021)
Background and objective: Venous thromboembolism is a leading cause of maternal morbidity and mortality. Few published articles have evaluated obstetricians’ compliance with thromboprophylaxis guidelines, especially after vaginal delivery. This study aimed to assess obstetricians’ adherence to postpartum thromboprophylaxis guidelines and correlate adherence with the risk factors for venous thromboembolism after vaginal and cesarean delivery. Methods: A cross-sectional study involving 981 women delivered at the Maternity Teaching Hospital, Erbil city, Kurdistan Region, Iraq, was conducted. Obstetricians’ compliance with the thromboprophylaxis guideline regarding dose, duration, and indications were recorded. We assessed the risk factors for thromboembolism using the 2015 Royal College of Obstetricians and Gynecologists guideline. Results: Medical thromboprophylaxis was required but not given to 93.2% of the women who delivered vaginally compared with 6.7% of the women who delivered by cesarean section. Women who delivered vaginally had a higher rate of age ˃ 36 years, parity of 3 and more, varicose vein, and current infection (P <0.001). The rates of preeclampsia, preterm labor, and prolonged labor were highest in the emergency cesarean section group (P <0.001). Factors associated with making a wrong decision were having no preeclampsia (odds ratio=15.4; 95% confidence interval=3.4–68.6), post-partum hemorrhage (odds ratio=15.3; 95% confidence interval=2.0–114.2), and vaginal delivery (odds ratio=250.2; 95% confidence interval=110.6–566.0). Conclusion: Obstetricians’ compliance with postpartum thromboprophylaxis in the hospital was low, especially after vaginal delivery.